2018
DOI: 10.3747/co.25.3883
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Interventions for Fatigue in Cancer and Transplantation: A Meta-Analysis

Abstract: Background Our objective was to determine whether, compared with control interventions, pharmacologic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 146 publications
1
45
0
2
Order By: Relevance
“…6,26 Three meta-analyses 15,20,22 addressed the addition of iron to an ESA. The remaining 12 meta-analyses 1,2,13,14,[16][17][18][19]21,[23][24][25] addressed ESA versus control (placebo or best standard therapy).…”
Section: Resultsmentioning
confidence: 99%
“…6,26 Three meta-analyses 15,20,22 addressed the addition of iron to an ESA. The remaining 12 meta-analyses 1,2,13,14,[16][17][18][19]21,[23][24][25] addressed ESA versus control (placebo or best standard therapy).…”
Section: Resultsmentioning
confidence: 99%
“…This result is encouraging after long frustration regarding fatigue reduction in oncology care with limited available pharmaceutical options. [28][29][30] Furthermore, this study also demonstrated benefit from minocycline in the cluster of the most severe symptoms, including pain, poor appetite, and shortness of breath, all with a medium ES.…”
Section: Discussionmentioning
confidence: 62%
“…6,26 Three meta-analyses 15,20,22 addressed the addition of iron to an ESA. The remaining 12 meta-analyses 1,2,13,14,[16][17][18][19]21,[23][24][25] addressed ESA versus control (placebo or best standard therapy). The quality of the meta-analyses varied based on AMSTAR2 criteria, such as assessment and discussion of bias and heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Aapro et al 13 reported an increased risk of death in ESA users (odds ratio, 1.20; 95% confidence interval [CI], 1.03 to 1.40) based on nine RCTs in patients with breast cancer. Meta-analyses consistently reported statistically significant reductions in fatigue with ESA use, 1,2,14,23 but the effect sizes were small and unlikely to be clinically important. 35 Little information about treatment intent is available from published studies, but one RCT 6 in the updated literature review restricted to patients with metastatic breast cancer and one meta-analysis 1 developed a decision model that incorporated intent of treatment.…”
Section: Recommendation 12mentioning
confidence: 95%